Peran Ombudsman Republik Indonesia Perwakilan Provinsi Jawa Tengah dalam Peningkatan dan Perbaikan Pelayanan Publik - Puruhito, Ghozali; Harsasto, Priyatno; Adnan, Muhammad (Journal of Politic and Government Studies, 2014)
AbstractThe study was backed by the objective conditions which showed the low qualityof public services in Central Java Province. Ombudsman of Indonesian Republic CentralJava Province Representative on their survey has come across many SKPD in CentralJava Province have not meet the services standards yet. As a public service watchdogagency aimed to increase the quality of public services, Ombudsman needs to beoptimized. Therefore, the purpose of the research is to know how the implementation ofthe duties and functions of Ombudsman of Indonesian Republic Central Java ProvinceRepresentative, how patterns of cooperation with other institution, and how the productof Ombudsman manifested in improvements to public services.This study is a qualitative research, technique of data collection by observation,interviews, documentary, and literature. The research result was that Ombudsman ofIndonesian Republic Central Java Province Representative on doing their roles has yetbeen maximum, preventive efforts through society education or socialization has yet toreach all stratums. It affects the intensity of report and complaint coming in toOmbudsman. The functioning of Ombudsman product as means to handle case until nowhas been adequate, despite there still Ombudsman product which tends to be ignored bythe reported party during written clarification stage. On the PDAM Tirta ModalSemarang case, Ombudsman worked well to settle it by mediation. Ombudsman insupporting their performance employs cooperation with all public service institution andprivate institution LSM Pattiro Semarang, the cooperation pattern is socialization andparticipation. Ombudsman product is realized on the improvement of public services byobliging public service institutions which has done maladministration to offercompensation to victims, and also to give assurance of improved public services in thefuture.To support optimization of Ombudsman of Indonesian Republic Central JavaProvince Representative, there need to be a synergy between existing stakeholders, an2enhancement of intensity of socialization to the public society and also an enhancementof human resource quality in the Ombudsman of Indonesian Republic Central JavaProvince Representative.